维生素C对A549细胞增殖、凋亡及Caspase-3、Survivin表达的影响 (Zhongguo Fei Ai Za Zhi, 2010)
BACKGROUND AND OBJECTIVE: It was proven that Vitamin C could inhibit the growth of many types of tumors as an antioxidant.The aim of this study is to explore role of Vitamin C in proliferation and apoptosis of lung carcinoma cell line A549 and the underlying mechanism. METHODS: A549 cells were cultured in vitro and incubated with Vitamin C.The cell viability was measured by growth curve and clonogentic assay.Flow cytometry was used to analyze cell cycle and detect apoptosis.The levels of expression of Caspase-3 mRNA and Survivin mRNA were detected by RT-PCR. RESULTS: Vitamin C of 400 μg/mL, 4 mg/mL significantly inhibited the growth of A549 cell lines (P=0.024, P=0.015, respectively).Flow cytometry showed that the cells major stagnation stayed in the G(0)/G(1) and S phase and the apoptotic rate increased with time prolonged.Vitamin C signifiantly up-ragulated the expression of Caspase-3 mRNA, but had no effect on Survivin mRNA. CONCLUSION: Vitamin C can inhibit the proliferation of A549, block A549 cells in G(0)/G(1) and S phase, and induce apoptosis of A549 cells.Apotosis occurred by up-ragulated the expressionof Caspase-3.